A Therapeutic Exploration into Conversation about God for Individuals with Complex Trauma in the Field of Psychology of Religion - Sara Jerebic (Bogoslovska Smotra)
Individuals with complex trauma develop highly individualized images of God, reflecting their internal conflicts, fears and the need for security. Some see God as insensitive or unjust, while others seek Him as a source of comfort, love and security not experienced in human relationships. Traumatic experiences are linked to forming internal beliefs about oneself, others and the world. Discussing God with individuals who have complex trauma requires a sensitive approach that takes into consideration their emotional state and experiences. Establishing a connection between God’s love and the healing process is crucial. Providing individuals with space to express emotions while respecting boundaries and encouraging trust-building is essential. When talking about God, language emphasizing warmth, tenderness and security should be employed to highlight God’s love and compassion. An adapted approach to spiritual growth that addresses individual needs and helps overcome traumatic experiences can foster positive coping. A psychologically sensitive approach supports the healing and spiritual growth of individuals with complex trauma.